2018
DOI: 10.1021/acsami.8b02435
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compound Gas-Sensing Properties of Bimodal Porous α-Fe2O3 with Ultrahigh Sensitivity and Fast Response

Abstract: Porous solid with multimodal pore size distribution provides plenty of advantages including large specific surface area and superior mass transportation to achieve high gas-sensing performances. In this study, α-FeO nanoparticles with bimodal porous structures were prepared successfully through a nanocasting pathway, adopting the bicontinuous 3D cubic symmetry mesoporous silica KIT-6 as the hard template. Its structure and morphology were characterized by X-ray diffraction, nitrogen adsorption-desorption, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…13,28 Furthermore, the paramagnetic properties of CuO, the number of chemisorbed oxygen species, the oxygen-vacancy site of the materials and the dipole moment of gas molecules are also possible factors for determining gas selectivity to a certain extent. 52,53 A noticeable character of long-term stability for a gas sensor is another crucially important role in practical applications. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13,28 Furthermore, the paramagnetic properties of CuO, the number of chemisorbed oxygen species, the oxygen-vacancy site of the materials and the dipole moment of gas molecules are also possible factors for determining gas selectivity to a certain extent. 52,53 A noticeable character of long-term stability for a gas sensor is another crucially important role in practical applications. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, some metal-based materials played a more and more important role in heterogeneous catalysis, such as Fe-based, Co-based, and Ni-based catalysts. It has been demonstrated that mesoporous metal-based materials possess widely applications owing to the large superficial area and porosity, which were widely used as microwave absorbers, electrode materials, , sensors, , and catalysts, etc. Over the course of the decades, lots of mesoporous silica materials were synthesized. , Inspired by ordered mesoporous silica materials, some ordered mesoporous metal oxides were successfully synthesized even if huge challenges exist.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Iron oxide is widely used in a wide range of applications in nanodevices due to its unique properties, such as water splitting, 24,25,30 supercapacitor, [31][32][33] lithium-ion battery, [34][35][36] catalyst, [37][38][39] photodetectors, 40 and gas sensor. [41][42][43] In our proposed approach, we synthesized Fe2O3 nanostructured films on ITO/glass substrates at various synthesis temperatures. The results show that Fe2O3 nanostructured films contain two mixtures of Fe 2+ and Fe 3+ cations and two trigonal (α) and cubic (γ) phases.…”
Section: Papermentioning
confidence: 99%